Searching for family farming in Argentina: chronicles of a technological innovation between two worlds - Goulet, Frédéric; Giordano, Gabriela (2018)
This paper proposes a contribution to the analysis of the processes that accompany the increasing fragmentation of agricultural worlds between contrasting models of development. To this end, we examine an area that has until now attracted little attention in this respect, that of the scientific and technological actors involved; we also look at original mechanisms which aim to create intersections between models of development. The paper is based on research carried out in Argentina, a country where there are two major contrasting models of development, embodied by the notions of agribusiness and family farming. We analyse the trajectory of a technological innovation in the field of machinery, based on the determination of agronomists and manufacturers to adapt agribusiness technologies to the needs of small family farmers. We study the attempts at problematisation and interessement that they make in relation to this public and its accompanying scientific and technical actors. These dynamics reveal contrasting approaches to innovation, technology and agricultural development. They also demonstrate the profound misunderstanding that exists between these two heterogeneous worlds.